PROGRAM GERAKAN PEKARANGAN PRODUKTIF BERBASIS URBAN FARMING - Puspita, Indah; Arsyadi, A; Aldila, Herman; Julianti, Erna (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2025)
The household-scale microgreen urban farming program was implemented in Lubuk Kelik Village, Bangka Regency, as a community empowerment initiative to improve family income and prevent stunting. This program was designed to utilize limited household land through the cultivation of microgreens, which are easy to grow, have a short harvesting period, and provide high nutritional value. The implementation methods included socialization, technical training, cultivation practices, mentoring, and evaluation of outcomes. The results showed an increase in participants’ knowledge and skills in managing microgreens independently. Some participants consumed the harvest to improve family nutrition, while others began marketing the products within their neighborhood, contributing to additional household income. This program has proven to support the availability of affordable nutritious vegetables while also strengthening community awareness of stunting prevention. Therefore, microgreen urban farming has the potential to become an applicable and sustainable model for community empowerment.